ANALISIS EFISIENSI PENGGUNAAN DANA MASYARAKAT UNTUK KEGIATAN DHARMA PENDIDIKAN DI INSTITUT PERTANIAN BOGOR - Hendro Sasongko, Mohammad Nur Hadi, Hermanto Siregar, (Jurnal Ekonomi, 2015)
This study focuses on measuring efficiency of all departements in Bogor Agricultural Institute using Data Envelopment Analysis (DEA) on the first stage and second stage is to determine the factors that influence the efficiency . DEA methodology is to evaluate the efficiency by comparing the all departement and using financial as an inputs and non-financial factors as an outputs. Second stage analysis using tobit regression because dependent factors are cencored between 0 to1 and independent factors uncencored. The results of first stage demonstrate that 54,29 % of departements in Bogor Agricultural University is efficiently operated in terms of academic factors during the period from 2012 to 2014, while 45,71 % is inefficient. And for the second stage the result are international accreditation and non academic staff are the factors can influence the efficiency of departements.